2019
DOI: 10.1097/01.ogx.0000557824.84633.0b
|View full text |Cite
|
Sign up to set email alerts
|

Livebirth After Uterus Transplantation From a Deceased Donor in a Recipient With Uterine Infertility

Abstract: (Abstracted from Lancet 2018;392:2697–2704) Infertility is common and affects about 10% to 15% of couples. In such couples, 1 in 500 women has infertility due to uterine causes, with uterine agenesis (Mayer-Rokitansky-Küster-Hauser [MRKH] syndrome), or due to hysterectomy, malformation, or the sequelae of infection or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
161
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(169 citation statements)
references
References 0 publications
4
161
0
4
Order By: Relevance
“…Ejzenberg et al. recently reported a healthy live birth, demonstrating that a uterus procured from a deceased donor can be functional . In this case, the donor—a 45‐year‐old woman who died from a subarachnoid hemorrhage—was deemed a good candidate because she had had three vaginal deliveries during her life and her blood type (O‐positive) matched that of the recipient.…”
Section: Uterus Transplantation From a Deceased Donormentioning
confidence: 89%
See 3 more Smart Citations
“…Ejzenberg et al. recently reported a healthy live birth, demonstrating that a uterus procured from a deceased donor can be functional . In this case, the donor—a 45‐year‐old woman who died from a subarachnoid hemorrhage—was deemed a good candidate because she had had three vaginal deliveries during her life and her blood type (O‐positive) matched that of the recipient.…”
Section: Uterus Transplantation From a Deceased Donormentioning
confidence: 89%
“…Ezjenberg et al. have also shown that the human uterus can remain functional after cold ischemia for four times longer than the average time after live donation (7 hours, 50 minutes vs 1 hour, 18 minutes) …”
Section: Uterus Transplantation From a Deceased Donormentioning
confidence: 99%
See 2 more Smart Citations
“…However, surrogacy is legally prohibited in China as per the 'Administrative Measures for Assisted Human Reproductive Technology' (2001). Moreover, even in the countries where surrogacy is permitted, UTx trials are also underway and have achieved live birth already in these countries . What is more, as for the surrogacy, the following problems regarding medical, ethical, legal and financial issues exist: the risk of communicable diseases from the surrogate mother to the child; the lifestyle of the surrogate; the risk of undermining the value of women's reproductive autonomy; psychological and physical risks for the surrogate mother and the child, potential custody battles and dispute in financial compensation for the surrogate mother .…”
Section: Why Utx In China?mentioning
confidence: 99%